Antifouling fabric and preparation method thereof
By using ultraviolet curing coating and covalent bond anchoring-dynamic repair mechanism in waterproof and oil-resistant fabrics, the functional degradation problem of existing fabrics under the action of ultraviolet and acid-base media is solved, and the long-term effectiveness and chemical stability of the fabric are improved.
Patent Information
- Application Number
- CN202510293800.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-06-27
Smart Images

Figure CN120211122A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti - pollution fabrics, and particularly relates to an anti - pollution fabric and a preparation method thereof. Background Art
[0002] Most existing functional fabrics focus on the development of properties such as waterproof and oil - proof, breathable and antibacterial, and warm - keeping. For the waterproof and oil - proof function, the mainstream technologies include post - finishing lamination methods (such as TPU, ePTFE film lamination) and yarn pretreatment methods (such as fluorocarbon compound coating, sol - gel method for hydrophobic modification).
[0003] In the prior art, as described in the utility model patent CN222499543U authorized by our company, by directly adding water - repellent masterbatch into the polyester spinning solution, melt - spinning is carried out to form a monofilament or multifilament structure of the whole - body water - repellent yarn, and then through weaving and heat treatment, the masterbatch undergoes a cross - linking reaction to endow the fabric with overall waterproof, oil - proof and anti - pollution properties.
[0004] Although this process avoids the easy - wear defect of traditional surface coatings through in - material modification, there are still essential limitations: First, the water - repellent function depends on the physical dispersion of fluorocarbon compounds (such as PTFE or fluorinated acrylate) in the masterbatch and the surface enrichment after heat treatment, and the binding between it and the polyester molecular chain is still through van der Waals forces or weak hydrogen bonds, lacking covalent bond anchoring; Second, under long - term ultraviolet irradiation, the C - F bonds on the surface of the yarn are prone to photo - oxidative cleavage, resulting in the migration and loss of fluorine elements and an increase in surface energy; Third, when permeated by acid - base media (such as sweat with pH of 4 - 6, industrial cleaning agents with pH>10), inorganic reinforcing phases such as nano - SiO2 in the masterbatch are prone to hydrolysis and dissolution, destroying the continuity of the internal hydrophobic network of the yarn.
[0005] Based on this, the present invention designs an anti - pollution fabric and a preparation method thereof to solve the above problems. Summary of the Invention
[0006] In view of the above - mentioned disadvantages existing in the prior art, the present invention provides an anti - pollution fabric and a preparation method thereof.
[0007] To achieve the above object, the present invention is realized through the following technical solutions:
[0008] An anti - pollution fabric sequentially includes a matrix fiber layer composed of water - repellent polyester spinning, and an ultraviolet - curable coating. The ultraviolet - curable coating includes a bottom bonding layer, an intermediate reinforcing layer and a surface protection layer;
[0009] The surface of the matrix fiber layer presents a composite rough structure of micron - level grooves and nano - level protrusions;
[0010] Bottom bonding layer: The perfluoropolyether prepolymer is bonded to the siloxane sites of the matrix fiber through a thiol-siloxane click reaction to form a covalent bond anchoring layer with a thickness of 100 - 300 nm;
[0011] Intermediate reinforcing layer: Hydroxylated boron nitride nanosheets are connected to the perfluoropolyether chain segments through ester bonds and disperse dynamic crosslinking agents to form a three-dimensional network resistant to acid and alkali corrosion;
[0012] Surface protective layer: The perfluoropolyether chain segments migrate directionally to the surface of the coating during the UV curing process to form a lotus leaf-like micro-nano structure.
[0013] Furthermore, the micron-sized grooves are formed by the synergistic action of the three-lobed orifice design of the spinneret and the spinning drawing process, with a groove depth of 0.5 - 3 μm and a helix angle of 15 - 30°.
[0014] Furthermore, the nano-sized protrusions are formed by the enrichment of nano-silica aerogel particles on the fiber surface and the induced phase separation during the cooling process of the modified polyester melt. The diameter of the protrusions is 50 - 200 nm, and the density is 10 3 -10 4 per mm 2 , the porosity of the nano-silica aerogel is 95 - 98%, the specific surface area is ≥800 m 2 / g, and its dispersion density in the modified polyester is 10 3 -10 4 per mm 3 .
[0015] A preparation method of the anti-fouling fabric includes the following steps:
[0016] S1: PET and a fluorosilane coupling agent are melt-blended in a twin-screw extruder at 280 - 300 °C and granulated to obtain a modified polyester masterbatch;
[0017] S2: The masterbatch is melt-spun through a three-lobed-honeycomb composite spinneret, controlling the spinning temperature at 290 - 310 °C and the cooling rate at 50 - 80 °C / s to form water-repellent fibers with a surface composite rough structure;
[0018] S3: The perfluoropolyether prepolymer, hydroxylated h-BN nanosheets, and dynamic crosslinking agent are dissolved in tetrahydrofuran and ultrasonically dispersed to form a coating solution;
[0019] S4: The coating solution is loaded onto the fiber surface by the dip-coating method, with a pulling rate of 5 - 10 mm / s, so that the solution fills the micron-sized grooves and coats the nano-sized protrusions;
[0020] S5: Irradiate with 308 nm ultraviolet light in a nitrogen atmosphere for 60 - 120 seconds, and synchronously stretch the fiber to trigger thiol-siloxane bonding and disulfide crosslinking;
[0021] S6: Heat press the fabric at 100 - 120 °C and 1 - 1.5 MPa for 10 - 15 minutes to activate the dynamic bond self - repair function and obtain the stain - resistant fabric.
[0022] Furthermore, in S3, the surface hydroxyl density of the hydroxylated h - BN nanosheets ≥ 4 per nm 2 , which is prepared by refluxing with concentrated sulfuric acid / hydrogen peroxide with a volume ratio of 3:1 at 80 °C for 6 hours.
[0023] Furthermore, in S5, the ultraviolet irradiation dose is 300 - 500 mJ / cm 2 , and the light intensity is 50 - 80 mW / cm 2 .
[0024] Furthermore, in S3, the dynamic cross - linker is a mixture of pentaerythritol tetrakis(thioglycolate) and bismaleimide with a mass ratio of 12 - 15:10 - 18.
[0025] Furthermore, in S6, the hot - pressing treatment is carried out in an environment with a relative humidity of 40 - 60%.
[0026] The present invention breaks through the technical bottleneck of existing functional fabrics. Through innovative structural design and the synergistic effect of multiple mechanisms, it realizes the improvement of the long - term effectiveness and environmental adaptability of stain - resistant performance, specifically manifested as:
[0027] 1. The present invention has a covalent anchoring - dynamic repair dual - mechanism to enhance durability. The surface hydroxyl groups of the hydroxylated h - BN nanosheets form a C - O - C covalent bond network with the polyester molecular chain, chemically immobilize fluorocarbons (such as perfluoropolyether) on the fiber matrix, replacing the traditional physical dispersion mode. The hot - pressing activates the dynamic exchange of thioester bonds to achieve in - situ repair of the C - F bond broken by UV photo - oxidation.
[0028] 2. The present invention has a two - dimensional barrier - moisture absorption regulation composite structure to enhance chemical stability. The h - BN nanosheets form a continuous two - dimensional barrier inside the fiber to inhibit the penetration of acid - base media. The honeycomb - like aerogel structure regulates the interfacial humidity through capillary action to avoid hydrolysis reactions.
[0029] 3. The present invention has a multi - level structure - function synergy to achieve a performance leap. The spinning with a trilobal spinneret forms a topological structure of micron - scale grooves and nano - scale protrusions, synergistically enhancing hydrophobicity and mechanical locking strength. The ultraviolet light triggers the synergistic effect of thiol - siloxane cross - linking and hydrothermal - pressing densification to construct a gradient functional interface. Description of the Drawings
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the accompanying drawings required for the description of the embodiments or the prior art. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other accompanying drawings can also be obtained based on these drawings.
[0031] Figure 1 It is a physical diagram of the present invention;
[0032] Figure 2 It is the stain resistance performance diagram of Embodiment 1 of the present invention;
[0033] Figure 3 It is the stain resistance performance diagram of Embodiment 1 of the present invention after ultraviolet aging;
[0034] Figure 4 It is the stain resistance performance diagram of Embodiment 2 of the present invention after acidification;
[0035] Figure 5 It is the stain resistance performance diagram of Embodiment 3 of the present invention after alkali rolling;
[0036] Figure 6 It is the stain resistance performance diagram of Embodiment 3 of the present invention;
[0037] Figure 7 It is the stain resistance performance diagram of Embodiment 3 of the present invention after ultraviolet aging;
[0038] Figure 8 It is the stain resistance performance diagram of Embodiment 1 of the present invention after acidification;
[0039] Figure 9 It is the stain resistance performance diagram of Embodiment 2 of the present invention after alkali rolling. Detailed implementation manners
[0040] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.
[0041] Embodiment 1: This embodiment provides a preparation method for a stain-proof fabric, including the following steps:
[0042] S1: Mix PET and a fluorosilane coupling agent (mass ratio 8:2) in a twin-screw extruder at 300 °C for melt blending, and granulate to obtain a modified polyester masterbatch;
[0043] S2: Melt-spin the masterbatch through a trilobal-honeycomb composite spinneret (hole diameter 100 μm), control the spinning temperature at 310 °C, and the cooling rate at 80 °C / s to form water-repellent fibers with a surface composite rough structure;
[0044] S3: Dissolve perfluoropolyether prepolymer (molecular weight 5000), hydroxylated h-BN nanosheets (15% by mass of hydroxylated boron nitride), and a dynamic crosslinking agent (5% by mass) in tetrahydrofuran, and ultrasonically disperse (800 W, 30 minutes) to form a coating solution;
[0045] Among them, the surface hydroxyl density of the hydroxylated h-BN nanosheets is 6 per nm 2 , and it is prepared by refluxing with concentrated sulfuric acid / hydrogen peroxide with a volume ratio of 3:1 at 80 °C for 6 hours;
[0046] Among them, in S3, the dynamic crosslinking agent is a mixture of pentaerythritol tetrathiol ester and bismaleimide with a mass ratio of 15:18;
[0047] S4: Use the dip-coating method to load the coating solution on the fiber surface, with a pulling rate of 10 mm / s, so that the solution fills the micron grooves and coats the nano-protrusions;
[0048] The micron-scale grooves are formed by the synergistic action of the trilobal orifice design of the spinneret (blade width 50 μm, blade gap 10 μm) and the spinning drawing process (drawing ratio 1:5), with a groove depth of 3 μm and a helix angle of 30°;
[0049] The nano-scale protrusions are formed by the enrichment of nano-silica aerogel particles (particle size 50 nm) on the fiber surface during the cooling process of the modified polyester melt and the induced phase separation, with a protrusion diameter of 200 nm and a density of 10 4 per mm 2 , the porosity of the nano-silica aerogel is 98%, the specific surface area is 800 m 2 / g, and its dispersion density in the modified polyester is 10 4 per mm 3 , and the nano-silica aerogel reduces the fiber surface energy by adsorbing environmental moisture to assist in maintaining hydrophobicity;
[0050] S5: Irradiate with 308 nm ultraviolet light for 120 seconds in a nitrogen atmosphere, and simultaneously draw the fiber (drawing ratio 1:5) to trigger thiol-siloxane bonding and disulfide crosslinking;
[0051] Among them, in S5, the ultraviolet irradiation dose is 500 mJ / cm 2 , and the light intensity is 80 mW / cm 2 ;
[0052] S6: Heat press the fabric at 120 °C and 1.5 MPa for 15 minutes to activate the dynamic bond self - repair function. The heat press treatment is carried out in an environment with a relative humidity of 60%. The wetting state of the fiber surface is regulated by the hygroscopicity of the aerogel to obtain a stain - resistant fabric.
[0053] Example 2: This example provides a method for preparing a stain - resistant fabric, which includes the following steps:
[0054] S1: Melt - blend PET and a fluorosilane coupling agent (mass ratio 8:2) in a twin - screw extruder at 280 °C and granulate to obtain a modified polyester masterbatch;
[0055] S2: Melt - spin the masterbatch through a trilobal - honeycomb composite spinneret (hole diameter 50 μm), control the spinning temperature at 290 °C, and the cooling rate at 50 °C / s to form water - repellent fibers with a surface composite rough structure;
[0056] S3: Dissolve a perfluoropolyether prepolymer (molecular weight 2000), hydroxylated h - BN nanosheets (15% mass ratio of hydroxylated boron nitride), and a dynamic cross - linker (5% mass ratio) in tetrahydrofuran and ultrasonically disperse (500 W, 30 minutes) to form a coating solution;
[0057] Among them, the surface hydroxyl density of the hydroxylated h - BN nanosheets is 4 per nm 2 , and it is prepared by refluxing with a 3:1 volume ratio of concentrated sulfuric acid / hydrogen peroxide at 80 °C for 6 hours;
[0058] Among them, in S3, the dynamic cross - linker is a mixture of pentaerythritol tetrakis(thioglycolate) and bismaleimide with a mass ratio of 12:10;
[0059] S4: Use the dip - coating method to load the coating solution on the fiber surface at a pulling rate of 5 mm / s, so that the solution fills the micro - grooves and coats the nano - protrusions;
[0060] The micro - grooves are formed by the synergistic action of the trilobal orifice design of the spinneret (blade width 20 μm, blade gap 5 μm) and the spinning drawing process (drawing ratio 1:3), with a groove depth of 0.5 μm and a helix angle of 15°;
[0061] The nano - protrusions are formed by the enrichment of nano - silica aerogel particles (particle size 10 nm) on the fiber surface during the cooling process of the modified polyester melt and the induced phase separation, with a protrusion diameter of 50 nm and a density of 10 3 per mm 2 , the porosity of the nano - silica aerogel is 95%, the specific surface area is 850 m 2 / g, and its dispersion density in the modified polyester is 10 3 per mm 3, nano-silica aerogel reduces the surface energy of fibers by adsorbing environmental moisture, assisting in maintaining hydrophobicity;
[0062] S5: Irradiate with 308 nm ultraviolet light for 60 seconds in a nitrogen atmosphere, and simultaneously stretch the fiber (draw ratio 1:3) to trigger thiol-siloxane bonding and disulfide crosslinking;
[0063] Among them, the ultraviolet irradiation dose in S5 is 300 mJ / cm 2 , and the light intensity is 50 mW / cm 2 ;
[0064] S6: Hot press the fabric at 100 °C and 1 MPa for 10 minutes to activate the dynamic bond self-healing function. The hot press treatment is carried out in an environment with a relative humidity of 40%. Utilize the hygroscopicity of the aerogel to regulate the surface wetting state of the fiber to obtain a stain-resistant fabric.
[0065] Example 3: This example provides a method for preparing a stain-resistant fabric, including the following steps:
[0066] S1: Melt-blend PET and a fluorosilane coupling agent (mass ratio 8:2) in a twin-screw extruder at 285 °C and granulate to obtain a modified polyester masterbatch;
[0067] S2: Melt-spin the masterbatch through a trilobal-honeycomb composite spinneret (hole diameter 80 μm), control the spinning temperature at 300 °C, and the cooling rate at 60 °C / s to form water-repellent fibers with a surface composite rough structure;
[0068] S3: Dissolve a perfluoropolyether prepolymer (molecular weight 4000), hydroxylated h-BN nanosheets (15% mass of hydroxylated boron nitride), and a dynamic crosslinking agent (5% mass) in tetrahydrofuran and ultrasonically disperse (700 W, 30 minutes) to form a coating solution;
[0069] Among them, the surface hydroxyl density of the hydroxylated h-BN nanosheets is 4 per / nm 2 , and it is prepared by refluxing with a volume ratio of 3:1 concentrated sulfuric acid / hydrogen peroxide at 80 °C for 6 hours;
[0070] Among them, in S3, the dynamic crosslinking agent is a mixture of pentaerythritol tetrathiol ester and bismaleimide with a mass ratio of 13:16;
[0071] S4: Use the dip-coating method to load the coating solution on the fiber surface at a pulling rate of 6 mm / s, so that the solution fills the micron grooves and coats the nano-protrusions;
[0072] The micron-scale grooves are formed by the combined action of the trilobal orifice design of the spinneret (blade width 30 μm, blade gap 9 μm) and the spinning drawing process (draw ratio 1:4). The groove depth is 2 μm and the helix angle is 20°;
[0073] The nanoscale protrusions are formed by the enrichment of nano-silica aerogel particles (particle size 30 nm) on the fiber surface during the cooling process of the modified polyester melt, inducing phase separation. The diameter of the protrusions is 100 nm and the density is 10 4 per mm 2 , the porosity of the nano-silica aerogel is 96%, the specific surface area is 800 m 2 / g, and its dispersion density in the modified polyester is 10 4 per mm 3 . The nano-silica aerogel reduces the fiber surface energy by adsorbing environmental moisture, assisting in maintaining hydrophobicity;
[0074] S5: Irradiate with 308 nm ultraviolet light for 100 seconds in a nitrogen atmosphere, and synchronously stretch the fiber (draw ratio 1:3) to trigger thiol-siloxane bonding and disulfide crosslinking;
[0075] Among them, the ultraviolet irradiation dose in S5 is 380 mJ / cm 2 , and the light intensity is 70 mW / cm 2 ;
[0076] S6: Hot press the fabric at 120 °C and 1.5 MPa for 12 minutes to activate the dynamic bond self-healing function. The hot press treatment is carried out in an environment with a relative humidity of 48%. Utilize the hygroscopicity of the aerogel to regulate the wetting state of the fiber surface to obtain the stain-resistant fabric.
[0077] Comparative Example 1: The difference from Example 3 is that hydroxylated h-BN nanosheets were not added in this comparative example;
[0078] This comparative example provides a method for preparing a stain-resistant fabric, including the following steps:
[0079] S1: Melt-blend PET and a fluorosilane coupling agent (mass ratio 8:2) in a twin-screw extruder at 285 °C and granulate to obtain a modified polyester masterbatch;
[0080] S2: Melt-spin the masterbatch through a trilobal-honeycomb composite spinneret (aperture 80 μm), control the spinning temperature at 300 °C, and the cooling rate at 60 °C / s to form water-repellent fibers with a surface composite rough structure;
[0081] S3: Dissolve a perfluoropolyether prepolymer (molecular weight 4000) and a dynamic crosslinking agent (mass ratio 5%) in tetrahydrofuran and ultrasonically disperse (700 W, 30 minutes) to form a coating solution;
[0082] Among them, in S3, the dynamic crosslinking agent is a mixture of pentaerythritol tetrathiol ester and bismaleimide with a mass ratio of 13:16;
[0083] S4: The coating solution is loaded onto the fiber surface by the dip-coating method at a pulling rate of 6 mm / s, allowing the solution to fill the micron-scale grooves and coat the nano-scale protrusions;
[0084] The micron-scale grooves are formed by the combined action of the three-lobed orifice design of the spinneret (blade width 30 μm, blade gap 9 μm) and the spinning drawing process (drawing ratio 1:4), with a groove depth of 2 μm and a helix angle of 20°;
[0085] The nano-scale protrusions are formed by the enrichment of nano-silica aerogel particles (particle size 30 nm) on the fiber surface during the cooling process of the modified polyester melt, inducing phase separation. The protrusion diameter is 100 nm and the density is 10 4 per mm 2 , the porosity of the nano-silica aerogel is 96%, the specific surface area is 800 m 2 / g, and its dispersion density in the modified polyester is 10 4 per mm 3 . The nano-silica aerogel reduces the fiber surface energy by adsorbing environmental moisture, assisting in maintaining hydrophobicity;
[0086] S5: Irradiate with 308 nm ultraviolet light for 100 seconds in a nitrogen atmosphere while simultaneously stretching the fiber (drawing ratio 1:3) to trigger thiol-siloxane bonding and disulfide crosslinking;
[0087] Among them, the ultraviolet irradiation dose in S5 is 380 mJ / cm 2 , and the light intensity is 70 mW / cm 2 ;
[0088] S6: Hot press the fabric at 120 °C and 1.5 MPa for 12 minutes to activate the dynamic bond self-healing function. The hot press treatment is carried out in an environment with a relative humidity of 48%. The fiber surface wetting state is regulated by the hygroscopicity of the aerogel to obtain the anti-fouling fabric.
[0089] Comparative Example 2: The difference from Example 3 is that in this comparative example, S6 is not carried out, that is, the dynamic bond self-healing function is not activated;
[0090] This example provides a method for preparing an anti-fouling fabric, including the following steps:
[0091] S1: Melt-blend PET and a fluorosilane coupling agent (mass ratio 8:2) in a twin-screw extruder at 285 °C and pelletize to obtain a modified polyester masterbatch;
[0092] S2: Melt-spin the masterbatch through a three-lobed-honeycomb composite spinneret (orifice diameter 80 μm), control the spinning temperature at 300 °C, and the cooling rate at 60 °C / s to form a water-repellent fiber with a surface composite rough structure;
[0093] S3: Dissolve perfluoropolyether prepolymer (molecular weight 4000), hydroxylated h-BN nanosheets (15% mass ratio of hydroxylated boron nitride), and a dynamic crosslinking agent (5% mass ratio) in tetrahydrofuran, and ultrasonically disperse (700 W, 30 minutes) to form a coating solution;
[0094] Among them, the surface hydroxyl density of the hydroxylated h-BN nanosheets is 4 per nm 2 , which is prepared by refluxing with concentrated sulfuric acid / hydrogen peroxide with a volume ratio of 3:1 at 80 °C for 6 hours;
[0095] Among them, in the above S3, the dynamic crosslinking agent is a mixture of pentaerythritol tetrathioester and bismaleimide with a mass ratio of 13:16;
[0096] S4: Use the dip-coating method to load the coating solution on the fiber surface at a pulling rate of 6 mm / s, so that the solution fills the micron grooves and coats the nano-protrusions;
[0097] The micron-scale grooves are formed by the combined action of the three-lobed orifice design (blade width 30 μm, blade gap 9 μm) of the spinneret and the spinning drawing process (drawing ratio 1:4), with a groove depth of 2 μm and a helix angle of 20°;
[0098] The nano-scale protrusions are formed by the enrichment of nano-silica aerogel particles (particle size 30 nm) on the fiber surface during the cooling process of the modified polyester melt and the induced phase separation. The protrusion diameter is 100 nm and the density is 10 4 per mm 2 , the porosity of the nano-silica aerogel is 96%, the specific surface area is 800 m 2 / g, and its dispersion density in the modified polyester is 10 4 per mm 3 , and the nano-silica aerogel reduces the fiber surface energy by adsorbing environmental moisture to assist in maintaining hydrophobicity;
[0099] S5: Irradiate with 308 nm ultraviolet light for 100 seconds in a nitrogen atmosphere, and simultaneously stretch the fiber (drawing ratio 1:3) to trigger thiol-siloxane bonding and disulfide crosslinking to obtain a stain-resistant fabric;
[0100] Among them, in the above S5, the ultraviolet irradiation dose is 380 mJ / cm 2 , and the light intensity is 70 mW / cm 2 .
[0101] Comparative Example 3: The difference from Example 3 is that neither hydroxylated h-BN nanosheets were added in this comparative example, nor was S6 carried out, that is, the dynamic bond self-healing function was not activated;
[0102] This example provides a method for preparing a stain-resistant fabric, including the following steps:
[0103] S1: PET and a fluorosilane coupling agent (mass ratio 8:2) are melt-blended in a twin-screw extruder at 285 °C and pelletized to obtain a modified polyester masterbatch;
[0104] S2: The masterbatch is melt-spun through a trilobal-honeycomb composite spinneret (hole diameter 80 μm), controlling the spinning temperature at 300 °C and the cooling rate at 60 °C / s to form water-repellent fibers with a surface composite rough structure;
[0105] S3: A perfluoropolyether prepolymer (molecular weight 4000) and a dynamic crosslinking agent (mass ratio 5%) are dissolved in tetrahydrofuran and ultrasonically dispersed (700 W, 30 minutes) to form a coating solution;
[0106] Among them, in S3, the dynamic crosslinking agent is a mixture of pentaerythritol tetrathioester and bismaleimide with a mass ratio of 13:16;
[0107] S4: The coating solution is loaded onto the fiber surface by the dip-coating method with a pulling rate of 6 mm / s, so that the solution fills the micron grooves and coats the nano-protrusions;
[0108] The micron-scale grooves are formed by the synergistic action of the trilobal orifice design of the spinneret (blade width 30 μm, blade gap 9 μm) and the spinning drawing process (drawing ratio 1:4), with a groove depth of 2 μm and a helix angle of 20°;
[0109] The nano-scale protrusions are formed by the enrichment of nano-silica aerogel particles (particle size 30 nm) on the fiber surface during the cooling process of the modified polyester melt and the induced phase separation, with a protrusion diameter of 100 nm and a density of 10 4 pieces / mm 2 , the porosity of the nano-silica aerogel is 96%, the specific surface area is 800 m 2 / g, and its dispersion density in the modified polyester is 10 4 pieces / mm 3 , and the nano-silica aerogel reduces the fiber surface energy by adsorbing environmental moisture to assist in maintaining hydrophobicity;
[0110] S5: Irradiate with 308 nm ultraviolet light for 100 seconds in a nitrogen atmosphere and simultaneously draw the fiber (drawing ratio 1:3) to trigger thiol-siloxane bonding and disulfide crosslinking to obtain a stain-resistant fabric;
[0111] Among them, in S5, the ultraviolet irradiation dose is 380 mJ / cm 2 , and the light intensity is 70 mW / cm 2 .
[0112] Control example: Select the company's authorized utility model patent CN222499543U.
[0113] Experimental example 1
[0114] The following table is the three-proof test form of the anti-fouling fabric of the present invention;
[0115] Water repellency level: GB / T 4745-2012 (test water temperature is 20°C);
[0116] Ease of detergency: FZ / T 01118-2012 washing method (staining substance: peanut oil);
[0117] Stain resistance: GB / T 30159.1-2013 liquid staining method (staining substance: dark soy sauce);
[0118] The fabrics of Examples 1-3 and Comparative Examples 1-3 prepared by the present invention were respectively subjected to ultraviolet (UV) radiation aging treatment (100 hours of UV aging, ASTM G154), acid treatment, and alkali treatment;
[0119] Among them, the specific acid treatment steps are: warm water at 50°C + acetic acid to adjust the pH to 3;
[0120] Soaking treatment: the temperature range is 50°C, and the time is 60 minutes (mechanical stirring, rotation speed 100 rpm).
[0121] Among them, the specific alkali treatment steps are:
[0122] Alkali padding: the impregnating solution is a caustic soda solution (22°Bé) at 25°C + penetrant (5881D), two-bath two-padding (padding rate 100-110%);
[0123] Cloth stretching treatment: apply tension in the weft direction (elongation rate 5%), and the action time is 60 seconds.
[0124] After the above aging treatment, the fabrics were washed and dried respectively and then subjected to the following tests, and the results are as follows:
[0125]
[0126]
[0127] Data analysis: From the data in the above table, it can be seen that the present invention melts and blends PET with a fluorosilane coupling agent to granulate, and forms a composite structure of micron grooves and nano-protrusions induced by nano-aerogel through spinning with a trilobal-honeycomb spinneret; a perfluoropolyether prepolymer and a dynamic crosslinking agent are formulated into a coating solution and loaded on the fiber surface by the dip-coating method; ultraviolet light synchronous irradiation is used to trigger the thiol-siloxane bonding and disulfide crosslinking, and then the hygroscopic regulation and dynamic bond self-healing functions of the aerogel are activated through hot and humid pressing treatment to form a long-lasting anti-fouling fabric with corrosion resistance and wear resistance;
[0128] The test data according to Embodiments 1-3 show that the antifouling fabric prepared by the present invention still has excellent weather resistance and chemical stability after UV accelerated aging, immersion in acidic media, and erosion treatment with alkaline solutions;
[0129] The comparative analysis of Comparative Examples 1-3 reveals that although the introduction of hydroxylated hexagonal boron nitride (h-BN) nanosheets can improve the UV aging resistance of the material, its individual effect on improving acid and alkali resistance is limited;
[0130] The dynamic bond hot pressing activation treatment significantly enhances the interfacial bonding strength by reconstructing the polymer molecular topological network;
[0131] It is worth noting that when the hydroxylated h-BN nanosheets form a synergistic system with the hot pressing process, the weather resistance of the material shows a significant leap: the C-F bond fracture rate after UV aging decreases, and the dissolution amount of nano-SiO2 in the acid-base environment decreases;
[0132] This synergistic mechanism achieves breakthroughs through the following paths:
[0133] First, the hydroxyl groups of the h-BN nanosheets form a covalent crosslinking network with the polyester molecular chain, effectively anchoring fluorocarbons and replacing the traditional physical dispersion mode;
[0134] Second, the dynamic thioester bond reconstruction induced by hot pressing repairs the photooxidation damage of the C-F bond caused by UV;
[0135] Third, the two-dimensional sheet structure of h-BN blocks the penetration of acid-base media and protects the integrity of the hydrophobic network of the inorganic reinforcement phase.
[0136] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements for some of the technical features; and these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A stain-resistant fabric, characterized in that: The invention comprises in sequence a base fiber layer composed of water-repellent polyester spinning, and an ultraviolet light-cured coating, wherein the ultraviolet light-cured coating comprises a bottom bonding layer, an intermediate reinforcing layer and a surface protective layer; The surface of the base fiber layer presents a composite rough structure of micron-scale grooves and nanometer-scale protrusions; The bottom bonding layer, the perfluoropolyether prepolymer is bonded to the siloxane sites of the matrix fiber through a mercapto-siloxane click reaction to form a covalent anchoring layer with a thickness of 100-300 nm; In the middle reinforcement layer, hydroxylated boron nitride nanosheets are connected to the perfluoropolyether segments through ester bonds and a dynamic crosslinking agent is dispersed to form a three-dimensional network resistant to acid and alkali corrosion; In the surface protective layer, the perfluoropolyether chain segments migrate directionally to the coating surface during the UV curing process to form a lotus leaf-like micro-nano structure.
2. The antifouling fabric according to claim 1, characterized in that: The micron-scale grooves are formed by the synergistic effect of the trilobal channel design of the spinneret and the spinning and drawing process, with a groove depth of 0.5-3 μm and a helical angle of 15-30°.
3. The antifouling fabric according to claim 2, characterized in that: The nano-scale protrusions are formed by the accumulation of nano-silicon dioxide aerogel particles on the fiber surface and induction of phase separation during the cooling process of the modified polyester melt. The protrusions have a diameter of 50-200 nm and a density of 10 3 -10 4 Pieces / mm 2 The nano-silica aerogel has a porosity of 95-98% and a specific surface area of ≥800m 2 / g, and its dispersion density in modified polyester is 10 3 -10 4 Pieces / mm 3 .
4. A method for preparing the antifouling fabric according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: melt-blending PET and fluorinated silane coupling agent in a twin-screw extruder at 280-300°C, and granulating to obtain modified polyester masterbatch; S2: The masterbatch is melt-spun through a trilobal-honeycomb composite spinneret, the spinning temperature is controlled at 290-310°C, and the cooling rate is 50-80°C / s to form a water-repellent fiber with a composite rough surface structure; S3: dissolving perfluoropolyether prepolymer, hydroxylated h-BN nanosheets, and a dynamic crosslinking agent in tetrahydrofuran, and performing ultrasonic dispersion to form a coating solution; S4: The coating liquid is loaded onto the fiber surface by the dipping-pulling method at a pulling rate of 5-10 mm / s, so that the solution fills the micro-grooves and covers the nano-protrusions; S5: irradiation with 308 nm UV light for 60-120 seconds in a nitrogen atmosphere, synchronously drawing the fibers to trigger mercapto-siloxane bonding and disulfide crosslinking; S6: hot pressing the fabric at 100-120°C and 1-1.5MPa for 10-15 minutes to activate the dynamic bond self-repairing function to obtain the anti-fouling fabric.
5. The method for preparing the antifouling fabric according to claim 4, characterized in that: The surface hydroxyl density of hydroxylated h-BN nanosheets in S3 is ≥ 4 / nm 2 , prepared by refluxing concentrated sulfuric acid / hydrogen peroxide at a volume ratio of 3:1 at 80°C for 6 hours.
6. The method for preparing the antifouling fabric according to claim 4, characterized in that: The ultraviolet radiation dose in S5 is 300-500 mJ / cm 2 , light intensity is 50-80mW / cm 2 .
7. The method for preparing the antifouling fabric according to claim 4, characterized in that: In the S3, the dynamic cross-linking agent is a mixture of pentaerythritol tetrathioate and bismaleimide in a mass ratio of 12-15:10-18.
8. The method for preparing the antifouling fabric according to claim 4, characterized in that: In S6, the heat pressing treatment is performed in an environment with a relative humidity of 40-60%.